2015
DOI: 10.18632/oncotarget.5495
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 links epithelial-to-mesenchymal transition and inflammatory signals to confer resistance to neoadjuvant trastuzumab and chemotherapy in HER2-positive breast cancer patients

Abstract: Patients with primary HER2-positive breast cancer benefit from HER2-targeted therapies. Nevertheless, a significant proportion of these patients die of disease progression due to mechanisms of drug resistance. MicroRNAs (miRNAs) are emerging as critical core regulators of drug resistance that act by modulating the epithelial- to-mesenchymal transition (EMT) and cancer-related immune responses. In this study, we investigated the association between the expression of a specific subset of 14 miRNAs involved in EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 41 publications
5
95
1
Order By: Relevance
“…It drives urgent need to detect new targets and treatment strategies. MiRNAs play a vital role in tumorigenesis, angiogenesis and drug resistance [3234], and are proved to be a useful biomarker in the diagnosis and prognosis of cancer. Recently, miRNAs or anti-miRNAs trafficked by microvesicles (MV) or other plasmids have been used for the treatment of various diseases in mouse models, including cancers [22, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…It drives urgent need to detect new targets and treatment strategies. MiRNAs play a vital role in tumorigenesis, angiogenesis and drug resistance [3234], and are proved to be a useful biomarker in the diagnosis and prognosis of cancer. Recently, miRNAs or anti-miRNAs trafficked by microvesicles (MV) or other plasmids have been used for the treatment of various diseases in mouse models, including cancers [22, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, miR‐21 mediates both trastuzumab and chemotherapy resistance in solid tumors via several mechanisms. It activates the IL‐6 – STAT3 – NF‐κB pathway and triggers PI3K ‐mediated signaling (De Mattos‐Arruda et al, ; Figure ). These data suggest that miR‐21 signaling sustains EMT and affects the tumor‐associated immune responses in HER2 + breast cancer.…”
Section: Mirnas and Resistance To Trastuzumabmentioning
confidence: 99%
“…8, 9, 10 Previous studies have revealed that numerous miRNAs are upregulated or downregulated in breast cancer, contributing to the initiation and development of the disease, as well as its drug sensitivity. 11, 12, 13 For instance, overexpression of miRNA-451 sensitizes breast cancer cells to doxorubicin, 14 and upregulation of miRNA-21 is associated with acquired trastuzumab resistance.…”
mentioning
confidence: 99%